INTERNALISASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Yusiani, Yusiani; Mastiah, Mastiah (FKIP UM Pontianak, 2026)
This study aims to describe the process internalizing character values in IPAS learning and to identify the character values integrated into learning for fourth-grade elementary school students. This research used a descriptive qualitative approach conducted at SD Negeri 26 Sidomulyo. The research subjects consisted of a fourth-grade teacher and fourth-grade students.” Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using technique triangulation to ensure data validity. The results showed that the internalization of character values was implemented through lesson planning, the teaching and learning process, and the teacher’s role modeling in attitudes and behavior. The character values internalized include responsibility, cooperation, discipline, honesty, and curiosity. These values were applied through learning activities such as group discussions, experiments, and interactions between teachers and students. Therefore, IPAS learning plays an important role in instilling character values in elementary school students.